2023
DOI: 10.3390/antiox12051078
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Thioredoxin-1 in Health and Disease

Abstract: Thioredoxin-1 (Trx-1) is a multifunctional protein ubiquitously found in the human body. Trx-1 plays an important role in various cellular functions such as maintenance of redox homeostasis, proliferation, and DNA synthesis, but also modulation of transcription factors and control of cell death. Thus, Trx-1 is one of the most important proteins for proper cell and organ function. Therefore, modulation of Trx gene expression or modulation of Trx activity by various mechanisms, including post-translational modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 168 publications
0
1
0
Order By: Relevance
“…Sustained activation of STAT3 in the nucleus is considered a hallmark of many human tumor types and leads to upregulation of a number of growth-promoting genes that contribute to tumor aggressiveness 16 , 36 . Recent studies have confirmed that intracellular Trx-1 is translocated to the nucleus in response to environmental stimuli, including oxidative stress 20 , 37 , 38 . Trx-1 is considered an anti-oxidant, anti-apoptotic effector, and redox regulator in signal transduction in response to H 2 O 2 stimulation 20 , 39 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sustained activation of STAT3 in the nucleus is considered a hallmark of many human tumor types and leads to upregulation of a number of growth-promoting genes that contribute to tumor aggressiveness 16 , 36 . Recent studies have confirmed that intracellular Trx-1 is translocated to the nucleus in response to environmental stimuli, including oxidative stress 20 , 37 , 38 . Trx-1 is considered an anti-oxidant, anti-apoptotic effector, and redox regulator in signal transduction in response to H 2 O 2 stimulation 20 , 39 .…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have confirmed that intracellular Trx-1 is translocated to the nucleus in response to environmental stimuli, including oxidative stress 20 , 37 , 38 . Trx-1 is considered an anti-oxidant, anti-apoptotic effector, and redox regulator in signal transduction in response to H 2 O 2 stimulation 20 , 39 . Our results showed Trx-1 nuclear translocation to be induced by treatment with IL-6, and that translocation to be suppressed after knockdown of STAT3 or specific deactivation of STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…TXN is indispensable for the normal functioning of both organs and tumors. It is strongly associated with various diseases, notably cancer, and ample evidence has been presented to underscore its significance in influencing the phenotype and prognosis of lung, gastrointestinal, and urological cancers ( 41 ). On the other hand, urinary TXN is regarded as a biomarker for diagnosing tubular redox dysregulation ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trx-1 induced activation of NOS3 and S-nitrosyation of CD95 leading to an increase of caspase-8 activity and caspase-3 activity [98] (Figure 8). This mechanism ultimately leads to reduced liver damage and promotes apoptosis of liver cancer cells [99].…”
Section: Role Of S-nitrosylation In Liver Cancermentioning
confidence: 99%